Complement C3 inhibition reduces complement activation in clinical platelet concentrates but does not counteract platelet storage lesions - Linnea I. Andersson; Per Sandgren; Dick J. Sjöström; Camilla Mohlin; Kim Hägerström; Ivar Tjernberg; Tom Eirik Mollnes; Per H. Nilsson (Platelets, 2025)
Platelet storage is associated with storage lesions, including platelet morphological changes and a gradual functional loss. We investigated the impact of complement C3 inhibition on complement activation and platelet storage lesions in clinical platelet concentrates. Platelet concentrates (n = 8) were prepared in PAS-E and stored for seven days at 22°C. Each concentrate was split in two, with the C3 inhibitor compstatin Cp40 added to one part, and the other serving as the control. Complement and platelet activation markers, platelet function, and metabolic measures were analyzed every second day. Cp40 significantly reduced C3bc and sC5b-9 levels, but not C4c, indicating inhibition of complement activation at the level of C3. However, Cp40 did not affect platelet-specific or metabolic measures. Surface expression of CD62P and NAP-2 release increased significantly over the storage time, whereas CD63 expression and PF4 and TSP-1 release remained stable. Platelet responses to TRAP-6 mediated PAR-1 activation and U46619 mediated TXA2R stimulation decreased over time, recorded as CD62P and CD63 expression and release of soluble factors. No drop in platelet count was observed, and metabolic markers remained within their critical limits. While C3 inhibition effectively reduced complement activation in stored platelet concentrates, it did not mitigate platelet storage lesions.